Modelling predictors of attitude and behavioural intention for halal skin care products / Azreen Jihan Che Mohd Hashim - Che Mohd Hashim, Azreen Jihan (Institute of Graduate Studies, UiTM, 2017)
Studies and interest on human behaviour in relation to halal industry have been increasing over the recent years. Drawing upon a social psychology theory, Theory Planned Behaviour (TPB) developed and congruity theory were employed as theoretical foundation for developing the present conceptual model. This thesis initially conceptualises key psychological factors that could predict and explain purchaser’s attitude. The data for this research were collected from 470 respondents who are user and non-user of halal skin care products in Klang Valley via drop off and collect survey technique. This research has shed new light in better understanding of the existing knowledge by incorporating relevant constructs as the predictors of attitude such as, spiritual intelligence, spiritual congruence, product image and product involvement. The significance of this study lies in the fact that, it attempts to identify and empirically investigate the predictors of attitude among the users and non-users. Subsequently, examines the predictors of intention such as attitude, subjective norm, and perceived behaviour control in a halal skin care products (compliance with Muslim Shariah requirement) context. Structural Equation Modeling (SEM) was utilised to test the hypothesised relationships among the constructs, as postulated in the research model. The results from hypothesis testing show that twelve hypothesised links were supported and two were not supported. With some minor modification, a plausible model that has a statistical and explanatory power for interpretation of results was confidently established. The findings from this study could offer several major contributions to the marketing and behaviour theory as well as to the marketing practitioners…